Verbal Fluency Performance in Normal Adult Population in Iran: Norms and Effects of Age, Education, and Gender - Saeedeh Shirdel; Setareh Esmaeeli; Kaveh Alavi; Pezhman Ghaemmaghami; Seyed Vahid Shariat (Basic and Clinical Neuroscience, 2022)
Introduction: Verbal fluency is a cognitive function that can be easily assessed at the bedside and provide valuable data for clinical assessment of various cognitive functions. We decided to provide a standardized test to assess verbal fluency in the Persian language, including both phonemic and semantic fluency subtests. Methods: First, three phonemes (/p/, /d/, and /ʃ/) and three categories (animals, fruits, and kitchen appliances) were selected based on a pilot study and a panel of specialists. Then, we selected 500 Persian-speaking participants (47.8% male) aged 18 to 65 years via a convenient sampling method from the general population. Participants were grouped according to age, gender, and education. They performed the verbal fluency test. Results: The Mean±SD number of generated words in letter fluency and semantic fluency was 8.3±4.1 and 18.0±5.5, respectively. Age, educational level, and mother tongue were associated with letter fluency. Semantic fluency was associated with age, gender, education level, and mother tongue. Conclusion: For a more reliable clinical assessment, we suggest using all three letters (phonemes) and three semantic categories for each subject, calculating the mean of the produced words, and comparing them with the suggested cut-off points provided for each subcategory. Age was negatively correlated with the number of generated words in letter fluency (r=-0.33; P<0.001) and semantic fluency tasks (r=-0.26; P<0.001). In the letter fluency task, there was no statistically significant difference between males and females according to the number of generated words (P=0.057). However, in semantic fluency, female participants generated more words (P=0.005). Mother tongue (Farsi) showed a significant effect both on letter fluency (t=5.55, P<0.001) and semantic fluency (t=9.41, P<0.001). Level of education had a significant association with both letter fluency (F=117.23, P<0.001) and semantic fluency (F=64.48, P<0.001).